1985
DOI: 10.1111/j.1524-4725.1985.tb03095.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Skin Temperatures Produced by New Skin Refrigerants

Abstract: Temperatures produced by Cryosthesia -30 degrees C, Cryosthesia -60 degrees C, and Frigiderm were measured in minipigs. Cryosthesia -60 degrees C and Cryosthesia -30 degrees C were both found to rapidly lower skin temperatures to levels that have been shown to cause cell injury, necrosis, and loss of melanocytes. Use of these agents requires extreme caution in dermabrasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Additional studies of Freon ‐ 12 and Freon ‐12‐based skin refrigerants have been reported by Strick and Moy 10 and Dzubow 11 . The sequence of events that led to these studies as well as our own has been discussed by Alt in a recent publication 1…”
Section: Discussionmentioning
confidence: 73%
“…Additional studies of Freon ‐ 12 and Freon ‐12‐based skin refrigerants have been reported by Strick and Moy 10 and Dzubow 11 . The sequence of events that led to these studies as well as our own has been discussed by Alt in a recent publication 1…”
Section: Discussionmentioning
confidence: 73%